Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300545
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Hurricane Risks

Abstract: Conveying uncertainty in information artifacts is difficult; the challenge only grows as the demand for mass communication through multiple channels expands. In particular, as natural hazards increase with changing global conditions, including hurricanes which threaten coastal areas, we need better means of communicating uncertainty around risks that empower people to make good decisions. We examine how people share and respond to a range of visual representations of risk from authoritative sources during hurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These issues should be addressed so that there are clear recommendations on how to present the zoomies and thus the presentation is standardized. In observing that track ensembles are rarely shared on social media as information about hurricanes (chosen only 3% of the time), Bica et al (2019) point to the potential role of unfamiliarity and lack of standardization with these line ensemble visualizations. To avoid a similar issue with zoomies, the displays should first be empirically evaluated and standardized.…”
Section: Discussionmentioning
confidence: 99%
“…These issues should be addressed so that there are clear recommendations on how to present the zoomies and thus the presentation is standardized. In observing that track ensembles are rarely shared on social media as information about hurricanes (chosen only 3% of the time), Bica et al (2019) point to the potential role of unfamiliarity and lack of standardization with these line ensemble visualizations. To avoid a similar issue with zoomies, the displays should first be empirically evaluated and standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons to previous events operate in a similar way by allowing users to compare Harvey to their previous hurricane and flooding experiences. Research indicates that reflections on previous disasters are common when faced with a potential disaster (Bica et al 2019), and these reflections can influence decision-making (Demuth et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that we rely on trust in, experience of, and knowledge about, a communicator to judge communications when we do not fully understand the message (Renn and Levine, 1991;Hocevar et al, 2017;Johnson et al, 2023). Research has also shown that individuals use various indicators of trust as a heuristic to evaluate scientific information, such as recognizing an organization's logo or stamp on a message or image (Bica et al, 2019). Any distrust in this agency or in the media carrying their message, due to political views or distrust of authority, can thus also impact this evaluation.…”
Section: Other Lessons For Communicationmentioning
confidence: 99%